Targeting Soluble Epoxide Hydrolase and Cyclooxygenases Enhance Joint Pain Control, Stimulate Collagen Synthesis, and Protect Chondrocytes From Cytokine-Induced Apoptosis - Tucker, Laura; Trumble, Troy N.; Groschen, Donna; Dobbs, Erica; Baldo, Caroline F.; Wendt-Hornickle, Erin; Guedes, Alonso G. P. (Frontiers in Veterinary Science, 2021)
Objective: To determine the symptomatic and disease-modifying capabilities of sEH and COX inhibitors during joint inflammation. Methods: Using a blinded, randomized, crossover experimental design, 6 adult healthy horses were injected with lipopolysaccharide (LPS; 3 μg) from E. coli in a radiocarpal joint and concurrently received the non-selective cyclooxygenase (COX) inhibitor phenylbutazone (2 mg/kg), the sEH inhibitor t-TUCB (1 mg/kg) or both (2 mg/kg phenylbutazone and 0.1, 0.3 and 1 mg/kg t-TUCB) intravenously. There were at least 30 days washout between treatments. Joint pain (assessed via inertial sensors and peak vertical forces), synovial fluid concentrations of prostanoids (PGE2, TxB2), cytokines (IL-1β, IL-6, TNF-α) and biomarkers of collagen synthesis (CPII) and degradation (C2C) were measured at pre-determined intervals over a 48-hour period. The anti-apoptotic effect of COX and sEH inhibitors was determined via ELISA technique in primary equine chondrocytes incubated with TNF-α (10 ng/ml) for 24 hours. Apoptosis was also determined in chondrocytes incubated with sEH-generated metabolites. Results: Combined COX and sEH inhibition produced significantly better control of joint pain, prostanoid responses and collagen synthesis-degradation balance compared to each compound separately. When administered separately, pain control was superior with COX vs. sEH inhibition. Cytokine responses were not different during COX and/or sEH inhibition. In cultured chondrocytes, sEH inhibition alone or combined with COX inhibition, but not COX inhibition alone had significant anti-apoptotic effects. However, sEH-generated metabolites caused concentration-dependent apoptosis. Conclusions: Combined COX and sEH inhibition optimize pain control, attenuate loss of articular cartilage matrix during joint inflammation and cytokine-induced chondrocyte apoptosis.